Anticancer efficacy of hydroxyethylthiamine diphosphate in vivo - Gevorkyan, L.; Gambashidze, K. (Experimental Oncology, 2014)
Aim: The aim of the presented article was investigation of anticancer efficacy of hydroxyethylthiamine diphosphate (HTD) in vivo. Materials and Methods: The study was carried out on 30 C57BL/6J mice subcutaneously transplanted with Ehrlich carcinoma. Animals were treated with intraperitoneal injections of the solution composed from pyruvic acid and thiamine bromide every other day during 10 days and thereafter, every day during 2 weeks. Treatment efficacy was evaluated by tumor growth inhibition. Results: In experimental animals treated with HTD, significant tumor growth inhibition has been registered: 73% at day 45th compared to the control group (p < 0.001). Conclusion: Treatment with HTD demonstrated high anticancer efficacy in vivo. Key Words: carcinogenesis, pH, hydroxyethylthiamine diphosphate, lipoic acid amide.